PREGABALIN AND ALPRAZOLAM IN TREATMENT OF GENERALIZED ANXIETY DISORDER IN PATIENTS WITH PARTIAL EPILEPSY - M. Ya. Kissin; I. I. Bondarenko (Эпилепсия и пароксизмальные состояния)
Hence anxiety disorders are frequently observed in the clinical picture of epilepsy these must be considered when choosing adequate therapy. Purpose of this study was evaluation therapeutic efficacy and adverse effects in people with epilepsy treated with pregabalin (PGB) 300 mg per day (20 patients), alprazolam (ALP) 1,5 mg per day (20 patients) and P (18 patients). In this study several characteristics had been evaluated in each group: seizure frequency, severity of anxiety disorder and adverse effects of the drugs administrated. In 50-days therapy of epileptic patients PGB demonstrated high efficacy and safety in treatment pharmacoresistant epilepsy comorbid with mental disorders specifically in treatment epilepsy with generalized anxiety disorders. PGB proved to be safer compared with ALP since no habituation elaborated. In durable therapy of anxiety disorders in epilepsy PGB must be recommended.